A fuzzy logic based goal achieving reactive navigation behaviour for a climbing mobile robot - 409044 Adel Ali S. Al-Jumaily; Shamsudin Mohd. Amin; Mohamed Khalil Mohd. Hani; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Elektrik
22